Endoscopic Treatment of Pilonidal Sinus Disease: State of Art and Review of the Literature - Manigrasso, Michele; Anoldo, Pietro; Cantore, Grazia; Chini, Alessia; D'Amore, Anna; Gennarelli, Nicola; Maione, Francesco; Marello, Alessandra; Schettino, Pietro; Sorrentino, Carmen; Vertaldi, Sara; Sosa Fernandez, Loredana Maria; et al. (Frontiers in Surgery, 2022)
Background: Pilonidal sinus disease (PSD) is a chronic troublesome pathology of the natal cleft of the sacrococcygeal region, with an estimated incidence of 26 cases in every 100,000 inhabitants. The aim of this review is to give a snapshot of the current literature on the endoscopic approach to PSD. Methods: A search on endoscopic treatment of pilonidal disease was performed according to PRISMA guidelines, adopting the following search terms: (pilonidal OR sacrococcygeal) and (endoscopic OR VAAPS OR EPSiT OR minimally invasive OR video-assisted OR video assisted). Results: Thirty-four articles were included in the final analysis, among which 23 were on adults and 11 were on pediatric population. The endoscopic approach is associated with painless postoperative pain, good aesthetic results, short time off work, and high patient satisfaction. Despite these advantages in short-term outcomes, results on recurrence rate in a long-term follow up are needed to definitively confirm the importance of this technique. Conclusions: The endoscopic approach is associated with significant postoperative advantages over other standard surgical approaches, and it should be included in the surgical portfolio for the treatment of PSD. According to the Italian guidelines, this technique could be considered as the gold standard for limited PSD. However, the favorable short-term-outcomes and lack of reliable data on long-term follow-up must be a stimulus to perform further high-quality studies to give definitive conclusions on this technique.